Mortality Predictors in Patients With COVID-19 Referred to the Emergency Department in Bandar Abbas, Southern Iran: A Single-Center Experience - Latife Jabbari; Leila AzizKhani; Saman Shamsipour; Saeed Hayati (Disease and Diagnosis)
Background: Determining the predictors of mortality in COVID-19 is a way of identifying high-risk patients. Previous studies reported comorbidities and old age as the essential components of COVID-19 mortality. The present study aimed to determine the predictors of mortality in patients with COVID-19 referred to the emergency department. Materials and Methods: The present descriptive-analytical study was conducted retrospectively on patients with confirmed COVID-19 referred to the Emergency Department of Shahid Mohammadi Hospital, Bandar Abbas, in 2019. Patient information, including age, gender, underlying disease, history of smoking, clinical symptoms, type of treatment, and laboratory findings, was extracted from the COVID registry. Results: In general, 2478 patients with COVID-19 were examined in this study. The average age of the patients was 52.57±16.41 years. Of them, 1371 people (55.3%) were men. The most common clinical symptom of the patients was shortness of breath (63.2%), and the most common underlying disease was hypertension (HTN) (24.3%). About 16.9% of the examined COVID-19 patients died. According to the results of multiple logistic regression analysis, with a 1-year increase in the age of the patients, the chance of death increased by 4.7% (P<0.001). In addition, dyspnea, HTN, ischemic heart disease, dyslipidemia, stroke, and malignancy increased the probability of death by 2.4, 1.6, 1.7, 3.6, 2.9, and 2.2 times, respectively (P<0.05). The most important predictor of mortality was C-reactive protein (CRP) 3+, which increased the probability of mortality in COVID-19 patients by almost 25 times (odds ratio [OR]=25.338, 95% CI=1.978–324.668, P=0.013). Moreover, with each unit increase in erythrocyte sedimentation rate (ESR), the chance of death in patients increased by 3.3% (P<0.001). On the other hand, among the clinical symptoms, anorexia (OR=0.711, 95% CI=0.506–0.999, P=0.050) and receiving macrolides (OR=0.212, 95% CI=0.091–0.492, P<0.001) had a protective role in mortality. Conclusion: Based on the results of this study, old age, dyspnea, HTN, ischemic heart disease, dyslipidemia, stroke, malignancy, CRP 3+, and high ESR were identified as predictors of mortality in COVID-19 patients. Of course, receiving macrolide and the presence of anorexia played a protective role in mortality in these patients.